Changes in nib acidification and biochemical composition during fermentation of pulp pre-conditioned cocoa (theobroma cacao) beans - Afoakwa, E.O.; Kongor, J.E.; Takrama, J.; Budu, A.S. (International Food Research Journal, 2013)
Studies were conducted to establish changes in nib acidification and biochemical composition (sugars concentration, proteins and free fatty acids) during fermentation of pulp pre-conditioned cocoa beans using a 4 x 3 full factorial experimental design with pod storage (0, 3, 7 and 10 days) and fermentation time (0, 3 and 6 days) as the principal factors. Non-volatile (titratable) acidity, pH, sugars (reducing, non-reducing and total sugars), proteins and free fatty acids of the beans were studied using standard analytical methods. Pod storage caused consistent increases in pH of the nibs at all fermentation times with consequential decrease in non-volatile (titratable) acidity. Bean fermentation from pods stored between 3-7 days resulted in cocoa nibs with pH between 5.10-5.36 with only minimal changes in FFA. However, fermentation significantly (p < 0.05) decreased the non-reducing sugars, total sugars and protein content of the beans whilst reducing sugars increased. Similarly, pod storage caused marginal reductions in total and non-reducing sugars with consequential increase in reducing sugars whiles protein content was reduced significantly. Storage of cocoa pod between 3-7 days with 6 days of fermentation led to considerable reductions in nib acidification, sugars (non-reducing and total sugars) and proteins with concomitant increases in reducing sugars and acceptable FFA levels. © All Rights Reserved.
Keywords: Acidification; Fermentation; Free fatty acids; Pod storage; Proteolysis; Pulp pre-conditioning; Sugars; Theobroma cacao